Familial hypomagnesaemia with hypercalciuria and nephrocalcinosis (FHHNC): Compound heterozygous mutation in the claudin 16 (CLDN16) gene - Konrad Martin A; Hampson Geeta; Scoble John (BMC Nephrology, 2008)
Abstract Background Familial hypomagnesaemia with hypercalciuria and nephrocalcinosis (FHHNC) is an autosomal recessive disorder of renal calcium and magnesium wasting frequently complicated by progressive chronic renal failure in childhood or adolescence. Methods A 7 year old boy was investigated following the findings of marked renal insufficiency and nephrocalcinosis in his 18-month old sister. He too was found to have extensive nephrocalcinosis with increased fractional excretion of magnesium: 12.4% (<4%) and hypercalciuria: 5.7 mmol (< 2.5/24 hours). He had renal impairment, partial distal renal tubular acidosis and defective urinary concentrating ability. Therapy with thiazide diuretics and magnesium supplements failed to halt the progression of the disorder. Both children subsequently underwent renal transplantation. Both children's parents are unaffected and there is one unaffected sibling. Results Mutation analysis revealed 2 heterozygous mutations in the claudin 16 gene (CLDN16) in both affected siblings; one missense mutation in exon 4: C646T which results in an amino acid change Arg216Cys in the second extracellular loop of CLDN16 and loss of function of the protein and a donor splice site mutation which changes intron 4 consensus splice site from 'GT' to 'TT' resulting in decreased splice efficiency and the formation of a truncated protein with loss of 64 amino acids in the second extracellular loop. Conclusion The mutations in CLDN16 in this kindred affect the second extra-cellular loop of claudin 16. The clinical course and molecular findings suggest complete loss of function of the protein in the 2 affected cases and highlight the case for molecular diagnosis in individuals with FHHNC.